Quantifying the influence of measured and unmeasured individual differences on demography. (3rd July 2015) - Plard, Floriane; Gaillard, Jean‐Michel; Coulson, Tim; Delorme, Daniel; Warnant, Claude; Michallet, Jacques; Tuljapurkar, Shripad; Krishnakumar, Siddharth; Bonenfant, Christophe; Childs, Dylan
Summary Demographic rates can vary not only with measured individual characters like age, sex and mass but also with unmeasured individual variables like behaviour, genes and health. Predictions from population models that include measured individual characteristics often differ from models that exclude them. Similarly, unmeasured individual differences have the potential to impact predictions from population models. However, unmeasured individual differences are rarely included in population models. We construct stage‐ and age‐structured models (where stage is mass) of a roe deer population, which are parameterized from statistical functions that either include, or ignore, unmeasured individual differences. We found that mass and age structures substantially impacted model parameters describing population dynamics, as did temporal environmental variation, while unmeasured individual differences impacted parameters describing population dynamics to a much smaller extent once individual heterogeneity related to mass and age has been included in the model. We discuss how our assumptions (unmeasured individual differences only in mean trait values) could have influenced our findings and under what circumstances unmeasured individual differences could have had a larger impact on population dynamics. There are two reasons explaining the relative small influence of unmeasured individual differences on population dynamics in roe deer. First, individual body mass and age both capture a large amount of individual differences in roe deer. Second, in large populations of long‐lived animals, the average quality of individuals (independent of age and mass) within the population is unlikely to show substantial variation over time, unless rapid evolution is occurring. So even though a population consisting of high‐quality individuals would have much higher population growth rate than a population consisting of low‐quality individuals, the probability of observing a population consisting only of high‐quality individuals is small.